Biaxially oriented laminated polyester film
By using biaxially oriented laminated polyester films, its specific A-layer and B-layer structure and particle distribution, the problems of pinholes, particle shedding and plane deterioration during the filming of ceramic green sheets are solved, achieving a more efficient mold release effect and a lower defect rate.
Patent Information
- Application Number
- CN202380051977.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-21
- Filing Date
- 2023-07-07
- Publication Date
- 2025-02-28
AI Technical Summary
In the process of film-film transformation of ceramic green sheets, especially when forming thin-film ceramic green sheets with a thickness of 1 μm or less, problems such as pinholes, particle shedding and deterioration of the plane-side of the mold release surface are prone to occur, resulting in an increase in the defect rate.
A biaxially oriented laminated polyester film is used as the release film, which has an A-layer and a B-layer structure. Layer A contains particles, with a surface roughness below 1.0 μm and a difference in particle size is within the range of 0.5 μm≤(Dmax-Dmin)≤5.5 μm. The B layer is a layer that does not contain particles with a particle size of 1.0 μm or more, and has a high surface smoothness. The ratio of the void size to the average particle size of the film is within the range of 0.5≤t/d≤3.0, and the thickness is more than 12 μm and less than 50 μm.
The generation of pinholes is effectively suppressed, the shedding of particles is reduced, and the planarity on the demolding surface side is maintained, thereby reducing the defect rate and improving the finished product quality of ceramic green sheets.
Smart Images

Figure BDA0005228993760000221 
Figure BDA0005228993760000231
Abstract
Description
Technical Field
[0001] The present invention relates to a biaxially oriented laminated polyester film for use as a release film for forming a resin sheet. In particular, the present invention can be used as a substrate in a release film for forming a resin sheet. Background Art
[0002] Release films based on polyethylene terephthalate films are used for the molding of ceramic products such as laminated ceramic capacitors and ceramic substrates. In recent years, with the miniaturization and high capacity of laminated ceramic capacitors, the thickness of ceramic green sheets has also tended to become thinner. As the green sheets become thinner, especially when it is desired to form thin film green sheets with a thickness of less than 1 μm, if there are coarse protrusions on the surface of the release side of the release film, when the ceramic slurry is applied to the release film, the slurry may be rejected, or pinholes may occur, and the green sheet may break when the green sheet is peeled off, etc. As a result, the defect rate of the laminated ceramic capacitor may sometimes be deteriorated.
[0003] In order to solve this problem, a film in which the surface to which a release agent is applied contains substantially no lubricant has been reported (for example, Patent Document 1).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2003-133170 Summary of the invention
[0007] Problem that the invention aims to solve
[0008] However, in recent years, various unprecedented problems have arisen in the further thinning of ceramic green sheets, especially in the attempt to form thin film ceramic green sheets with a thickness of less than 1 μm. For example, there is a problem of pinholes in thin film ceramic green sheets. For example, when winding, it is believed that pinholes are formed by the transfer of coarse protrusions on the surface opposite to the demolding surface to the demolding surface side, the falling off of particles from the surface of the film, and the deterioration of the planarity of the demolding surface side.
[0009] The present invention was made against the background of the technical problems of the prior art, and has as its object to provide a biaxially oriented laminated polyester film capable of suppressing the generation of pinholes more effectively than the prior art in the production process of a resin sheet such as a ceramic green sheet.
[0010] The present inventors have conducted intensive studies to solve the above-mentioned technical problems and, as a result, have found that the above-mentioned object can be achieved by a release film having the following structure, thereby completing the present invention.
[0011] Solutions for solving problems
[0012] That is, the present invention consists of the following constitutions.
[0013] [1] A biaxially oriented laminated polyester film used as a release film for forming a resin sheet, the biaxially oriented laminated polyester film comprising an A layer and a B layer.
[0014] The A layer contains particles,
[0015] The maximum peak height (SRp) of the surface roughness of the A layer is 1.0 μm or less,
[0016] The relationship between the maximum size Dmax and the minimum size Dmin of the particles in the polyester film satisfies the following formula 1: 0.5 μm ≤ (Dmax - Dmin) ≤ 5.5 μm (Formula 1). [2]
[0018] The biaxially oriented laminated polyester film according to [1], wherein the layer B is a layer substantially free of particles having a particle size of 1.0 μm or more,
[0019] The maximum peak height SRp of the surface of the B layer is 1.0 μm or less. [3]
[0021] The biaxially oriented laminated polyester film according to any one of [1] to [3], wherein the ratio of the void size t in the film to the average particle size d satisfies the following formula 2:
[0022] 0.5≤t / d≤3.0 (Formula 2). [4]
[0024] The biaxially oriented laminated polyester film according to [1], wherein the film thickness is 12 μm or more and 50 μm or less. [5]
[0026] A release film comprising the biaxially oriented laminated polyester film described in any one of [1] to [5] and a functional layer.
[0027] The functional layer is disposed on the layer B side of the biaxially oriented laminated polyester film.
[0028] Effects of the Invention
[0029] The present invention provides a biaxially oriented laminated polyester film for a release film for forming a resin sheet, which can reduce the falling off of particles and suppress coarse protrusions. For example, the present invention can suppress the formation of pinholes caused by the transfer of coarse protrusions on the opposite release surface to the release surface side, can suppress the falling off of particles from the film surface, and further can suppress the formation defects caused by the deterioration of the planarity on the release surface side. DETAILED DESCRIPTION
[0030] Hereinafter, embodiments of the present invention will be described in detail.
[0031] The present invention is a biaxially oriented laminated polyester film used as a release film for forming a resin sheet, wherein the biaxially oriented laminated polyester film comprises an A layer and a B layer.
[0032] The A layer contains particles, and the maximum peak height (SRp) of the surface roughness of the A layer is 1.0 μm or less,
[0033] The relationship between the maximum size Dmax and the minimum size Dmin of the particles in the polyester film satisfies the following formula 1:
[0034] 0.5μm≤(Dmax-Dmin)≤5.5μm (Formula 1).
[0035] The biaxially oriented laminated polyester film of the present invention is a biaxially oriented laminated polyester film (hereinafter also referred to as a base film) formed by a laminated structure having at least an A layer and a B layer. For example, a release film can be obtained by having a release layer on one side of the base film of the present invention. Preferably, the functional layer is disposed on the B layer side of the polyester film, for example, the release layer is laminated on the B layer side of the polyester film.
[0036] In one embodiment, the polyester film may have an A layer, a C layer (intermediate layer), and a B layer in this order, and a functional layer such as a release layer may be laminated on the surface of the B layer.
[0037] As the substrate film, for example, films composed of polyethylene terephthalate, polybutylene terephthalate, polyethylene 2,6-naphthalate or copolymers containing the constituent components of these resins as the main components can be cited. Among them, biaxially stretched polyethylene terephthalate films are particularly preferred from the perspectives of mechanical properties, heat resistance, transparency, price, etc. The A layer and the B layer in the present invention may contain different resins as the main components or the same resin as the main components.
[0038] When a copolymer is used in a substrate film, as its dicarboxylic acid component, for example, aliphatic dicarboxylic acids such as adipic acid and sebacic acid; aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, and 2,6-naphthalene dicarboxylic acid; polyfunctional carboxylic acids such as trimellitic acid and pyromellitic acid. In addition, as a diol component, for example, fatty acid diols such as ethylene glycol, diethylene glycol, 1,4-butanediol, propylene glycol, and neopentyl glycol; aromatic diols such as p-xylene glycol; alicyclic diols such as 1,4-cyclohexanedimethanol; polyethylene glycol with an average molecular weight of 150 to 20,000 can be listed. The weight ratio of the copolymer components of the preferred copolymer is less than 20% by weight. By less than 20% by weight, good film strength, transparency, and heat resistance can be obtained.
[0039] The intrinsic viscosity of the resin pellets used to make the substrate film is preferably in the range of 0.45 dl / g or more and 0.70 dl / g or less. When the intrinsic viscosity is 0.45 dl / g or more, there is a tendency to improve tear resistance. On the other hand, when the intrinsic viscosity is 0.70 dl / g or less, it is possible to suppress the increase in filter pressure and appropriately perform the high-precision filtration described below. The intrinsic viscosity is preferably 0.50 dl / g or more and 0.70 dl / g or less, more preferably 0.52 dl / g or more and 0.64 dl / g or less.
[0040] The thickness of the biaxially oriented laminated polyester film (substrate film) of the present invention is preferably 12 μm or more and 50 μm or less, more preferably 15 μm or more and 38 μm or less, and more preferably 19 μm or more and 33 μm or less. If the thickness of the film is 12 μm or more, there is no risk of deformation due to heat during film production or processing steps or molding, so it is preferred. On the other hand, if the thickness of the film is 50 μm or less, the amount of film discarded after use will not increase excessively, which is preferred in reducing the environmental burden.
[0041] The thickness of each layer is preferably 5.0 μm or more, and more preferably 10 μm or more, for example, for the B layer on which the release layer can be laminated. When the thickness of the B layer is within this range, the smoothness of the B layer can be well maintained.
[0042] The thickness of the particle-containing A layer is a thickness capable of maintaining the maximum peak height (SRp) of the present invention, and is, for example, 1 μm or more and 10 μm or less.
[0043] In one embodiment, the surface roughness (SRp) of the A layer is 1.0 μm or less, more preferably 0.6 μm or less, for example 0.05 μm or less, and may be 0.01 μm or less.
[0044] On the other hand, the surface roughness (SRp) of the B layer may be 1 nm or more. For example, it may be 1 nm or more and 0.01 μm or less.
[0045] By setting the surface roughness (SRp) of the B layer to be within this range, concave transfer onto a resin sheet such as a ceramic sheet can be suppressed, and shape defects of the ceramic sheet or the like that may be caused by the concave transfer portion can be suppressed.
[0046] In one embodiment, the biaxially oriented laminated polyester film of the present invention has other layers in addition to layer A and layer B, and may have a laminated structure of three or more layers. For example, the base film may have a laminated structure having layer A, layer C (intermediate layer), and layer B in this order.
[0047] In this scheme, the C layer as the intermediate layer may also contain particles. However, the particle size of the C layer needs to be selected within a range that does not damage the surface shape of the B layer. For example, if the C layer contains foreign matter larger than 20 μm, it will cause large protrusions to form on the A layer and the B layer, so such particles need to be removed.
[0048] In one embodiment, the layer B of the laminated functional layer, such as the release layer, does not substantially contain particles with a particle size of 1.0 μm or more. Preferably, the surface layer B does not substantially contain inorganic particles with a particle size of 1.0 μm or more. By not containing inorganic particles with a particle size of 1.0 μm or more in the surface layer B, it is possible to prevent the particle shape in the substrate from being transferred to the resin sheet and causing defects.
[0049] In one embodiment, particles with a particle size of less than 1.0 μm and greater than 1 nm may also be present in the surface layer B on which the release layer can be laminated. By including particles with a particle size of less than 1.0 μm and greater than 1 nm, such as inorganic particles, the surface layer B can reduce the situation where the particle shape in the substrate is transferred to the resin sheet and causes defects. It should be noted that in one embodiment, the resin sheet is laminated on the functional layer laminated on the surface layer B.
[0050] In one embodiment, it is also preferred that the surface layer B does not contain particles having a particle size of less than 1.0 μm. This can more effectively prevent the particle shape in the substrate from being transferred to the resin sheet and causing a defect.
[0051] In one embodiment, the polyester film substrate is preferably a laminated film having a surface layer B substantially free of inorganic particles on at least one surface. This can more effectively prevent the particle shape in the substrate from being transferred to the resin sheet and causing defects.
[0052] For example, the surface layer B substantially containing no particles having a particle size of less than 1.0 μm preferably also substantially contains no particles having a particle size of 1.0 μm or more.
[0053] Here, in the present invention, "substantially free of particles" means, for example, in the case of inorganic particles smaller than 1.0 μm, that the content is 50 ppm or less, preferably 10 ppm or less, and most preferably below the detection limit when the inorganic elements are quantified by X-ray fluorescence analysis. This is because sometimes, even if particles are not actively added to the film, contaminants from foreign matter, dirt attached to the production line or equipment in the manufacturing process of the raw resin or film will peel off and mix into the film. In addition, "substantially free of particles with a particle size of 1.0 μm or more" means that particles with a particle size of 1.0 μm or more are not actively included.
[0054] The B layer on which the release layer can be laminated is preferably extremely smooth. The number of protrusions with a height of 10 nm or more relative to the average height of the B layer is preferably 5×10 2 Pieces / mm2 The following. By setting the number of protrusions to this range, the necessary amount of release agent to form the release layer can be evenly applied including the protrusions, and the original release property of the release agent can be brought into play. In addition, by setting the number of protrusions on the B layer to the above range, the protrusions on the surface of the release layer can be reduced, and the concave transfer to the resin sheet such as the ceramic sheet can be suppressed, and the shape defects of the ceramic sheet etc. that may be caused by the concave transfer part can be suppressed.
[0055] Examples of the types of particles contained in the A layer, the B layer, and the intermediate layer of the substrate film include inorganic particles such as silicon dioxide, calcium carbonate, kaolin, titanium oxide, and aluminum oxide, but are not limited thereto.
[0056] The A layer contains particles, and the maximum peak height (SRp) of the surface roughness of the A layer is less than 1.0 μm, for example, greater than 0.3 μm and less than 1.0 μm. Preferably, it is greater than 0.5 μm and less than 0.8 μm. By having such a condition of the maximum peak height (SRp) of the surface roughness of the A layer, it is possible to suppress the coarse protrusions of the A layer, for example, it is possible to suppress the formation of pinholes caused by the transfer of the coarse protrusions of the anti-demolding surface to the demolding surface side, and further it is possible to suppress the formation defects caused by the deterioration of the planarity of the demolding surface side.
[0057] In the biaxially oriented laminated polyester film of the present invention, the relationship between the maximum size Dmax and the minimum size Dmin of particles in the polyester film satisfies the following formula 1.
[0058] 0.5μm≤(Dmax-Dmin)≤5.5μm (Formula 1)
[0059] In one embodiment, when the A layer and / or the intermediate layer (C layer) in the biaxially oriented laminated polyester film of the present invention contains particles, the above relationship (Formula 1) can be exhibited.
[0060] For example, when the particles contained in layer A have the relationship of (Formula 1), the coarse protrusions of layer A can be greatly reduced, the falling of particles can be suppressed, and the generation of pinholes in resin sheets such as ceramic green sheets can be suppressed. Regarding layer C, it is also preferred that the relationship between the maximum size Dmax and the minimum size Dmin of the particles in the polyester film satisfies the following Formula 1.
[0061] 0.5μm≤(Dmax-Dmin)≤5.5μm (Formula 1)
[0062] Here, Dmax and Dmin in 0.5≤(Dmax-Dmin)≤5.5 are both expressed in μm. In the specification, only the value of (Dmax-Dmin) may be shown, and the value of (Dmax-Dmin) is also expressed in μm.
[0063] By having the relationship shown in (Formula 1) for the particles in layer A, it is possible to suppress the formation of pinholes caused by the transfer of coarse protrusions of the reverse demolding surface (layer A) to the demolding surface side, and also to suppress the particles from falling off the film, especially when forming a thin film ceramic raw sheet with a thickness of less than 1 μm.
[0064] Usually, when the substrate film is bent during the winding process of manufacturing the film or when it comes into contact with the conveyor roller, there is a tendency that the load on the particles becomes larger and it is easy to fall off from the film. Although it should not be limited to a specific theory for explanation, the inventors have found that, for example, the particles in layer A have a relationship shown in (Formula 1), and in the state where the film is bent as described above, the load on the particles in layer A can be dispersed, and the falling of particles can be reduced. In addition, if the present invention is used, the winding property can be improved while reducing the falling of particles, pinholes on the ceramic green sheet during winding can be suppressed, and the falling of particles during unwinding can be reduced.
[0065] On the other hand, when the particles in layer A do not show the relationship shown in (Equation 1), although the explanation should not be limited to a specific theory, the load on the particles in layer A may not be dispersed when the film is bent, and the particles may slide off.
[0066] Furthermore, in layer A, the above effects can be more significantly exerted by particles satisfying the various conditions described in this specification. For example, the average particle size of layer A and / or the relationship between the maximum size Dmax and the minimum size Dmin of particles in layer A satisfy the relationship described below.
[0067] In one embodiment, in order to make the particles in layer A have the relationship shown in (Formula 1), the average primary particle size of the particles contained in layer A is preferably 3.0 μm or less, for example, preferably 1.4 μm or less, and more preferably 1.0 μm or less. In addition, the average primary particle size of the particles contained in layer A is greater than 0.3 μm, and is greater than 0.35 μm. Preferably, it is greater than 0.3 μm and less than 3.0 μm. In addition, the above numerical ranges can also be appropriately combined.
[0068] By having such an average primary particle size, winding wrinkles can be suppressed and the generation of coarse protrusions can be suppressed. As a result, suppression of pinholes, good winding / unwinding properties, and suppression of particle shedding can be achieved in a well-balanced manner.
[0069] In addition, the average primary particle size (μm) in the present invention can be measured by using a light transmission type centrifugal sedimentation type particle size distribution measuring instrument (manufactured by Shimadzu Corporation, trade name "SRA-CP3 type") to fully disperse the particle powder in the ethylene glycol slurry by high-speed stirring. The cumulative 50% in this measurement can be used as the measurement result (sometimes expressed as D50).
[0070] In the present invention, the relationship between the maximum size Dmax and the minimum size Dmin of particles in the thin film satisfies the following formula 1.
[0071] 0.5μm≤(Dmax-Dmin)≤5.5μm (Formula 1).
[0072] The range of (Dmax-Dmin) may be 1.0 μm or more and 5.0 μm or less, for example, 1.2 μm or more and 5.0 μm or less, or 1.4 μm or more and 5.0 μm or less.
[0073] When (Dmax-Dmin) is in the range of 0.5 μm or more and 5.5 μm or less, the load on the particles can be reduced during the winding process during film production or when the particles come into contact with a conveying roll, thereby preventing the particles from falling off the film.
[0074] In addition, after the film is manufactured, the film of the present invention is stored in a roll until the release layer is formed, which can prevent the particles from sliding off. Therefore, it is possible to inhibit the particles from falling off the A layer from adhering to the surface of the B layer that can form the release layer, and the high smoothness of the B layer can be maintained in the storage state of the base film. By maintaining the high smoothness of the B layer, a release layer with higher smoothness can be formed, which can prevent the generation of pinholes on the ceramic green sheet and the like.
[0075] In this way, since it is possible to suppress the falling of particles when the film is bent (when rolled into a roll), it is possible to suppress the adhesion of the falling particles to the resin sheet such as the ceramic green sheet, thereby suppressing the damage to the function of the resin sheet. In addition, in the manufacturing and transportation system, it is possible to reduce the pollution caused by the particles.
[0076] On the other hand, the average particle size (D50), the maximum size Dmax and the minimum size Dmin of the particles in the film refer to the diameter of the particles added to the resin composition constituting the film in any process before the film is manufactured. In addition, after the film is manufactured, it refers to the diameter of the particles present in the film. For example, the average particle size (D50) of the particles present in the surface layer A refers to the diameter of the particles as a whole, including the parts covered by the resin and the parts not covered by the resin.
[0077] In one embodiment, when a film containing particles is stretched uniaxially or biaxially, the following formula 2 is preferably satisfied, where the size of the voids causing separation between the resin and the particles is t and the average particle size in the film is d.
[0078] 0.5≤t / d≤3.0 (Formula 2).
[0079] For example, the relationship t / d may be 2.8 or less, 2.5 or less, or 2.4 or less. On the other hand, the relationship t / d may be 1.0 or more, or 1.2 or more.
[0080] The relationship of t / d may preferably be 1.0 or more and 2.8 or less.
[0081] By making the relationship between the void size t and the average particle size d in the film within the above range, it is possible to suppress the falling of particles during the film winding process and demolding. In addition, the film undulation component caused by the void can be appropriately formed, and the gas exhaust property of the film can be well maintained. Since the present invention can show good gas exhaust property of the film, it is possible to suppress the winding wrinkles generated when the film is stacked into a roll. By eliminating the film roll, the flatness can be improved, and the demolding layer can be uniformly formed, thereby preventing the generation of pinholes on the ceramic green sheet and the like.
[0082] In a preferred embodiment, the average particle size d in the film refers to the average particle size d in the A layer. In addition, the void size t caused by peeling between the resin and the particles refers to the void size existing in the film after the film is stretched. In one embodiment, the void size t existing in the A layer after stretching can be applied. It should be noted that the A layer after stretching refers to the layer corresponding to the A layer before stretching. In one embodiment, voids may be generated in the surface layer A having particles. Although not limited to a specific method, voids usually exist around the particles, and more specifically, the voids exist in a manner of surrounding the particles.
[0083] When the surface layer B does not contain particles, there are substantially no voids in the surface layer B. However, there are cases where very small voids are generated in the surface layer B due to contamination components or the like.
[0084] As the surface modification of the particles, it is desirable to modify them using commonly used polyacrylic acid, silane coupling agents, etc. The heat-resistant temperature of the surface treatment agent is preferably 250° C. or higher, and more preferably 300° C. or higher, as measured by the 2% weight loss temperature. By setting the heat-resistant temperature of the surface treatment agent to such a condition, it is possible to prevent the surface treatment agent from disappearing due to the thermal history during melt extrusion, and to obtain good dispersibility and inhibition of particle shedding.
[0085] The drying temperature of the pellets containing particles is preferably 130° C. or higher and within 30 hours, more preferably within 10 hours.
[0086] The melt extrusion temperature is preferably within +70°C, more preferably within +50°C, of the melting peak temperature obtained when the resin is heated at 20°C / min using a differential scanning calorimeter (DSC).
[0087] The void size ratio of an unstretched film formed at a shear rate of 50 to 4000 (1 / sec) in a T-die in a melt extrusion step is 0, and voids are formed in a subsequent stretching step. The voids can be observed, for example, by observing a cross section of the film using an electron microscope.
[0088] The film may be stretched in the longitudinal and transverse directions simultaneously or sequentially. When the film is stretched sequentially, the order of stretching may be arbitrary, but considering the size of the equipment, the order of stretching first in the longitudinal direction and then in the transverse direction is preferred.
[0089] The longitudinal stretching ratio is preferably 2.0 to 5.0 times, more preferably 3.0 to 3.8 times, and the transverse stretching ratio is preferably 3.5 to 5.0 times, more preferably 4.0 to 4.8 times.
[0090] In one embodiment, the stretching ratio in the longitudinal direction is lower than the stretching ratio in the transverse direction. Although the mechanism has not yet been analyzed, there is a tendency that the particles can be prevented from sliding down by stretching under such conditions.
[0091] The content of particles in the outermost layer, for example, layer A, is not particularly limited. In order to stabilize the operability in film manufacturing, it is preferably 8000 ppm or less, and more preferably 6500 ppm or less. In addition, the content is preferably 1000 ppm or more, for example, 1500 ppm or more. By having the particle content of layer A in such a range, it is possible to reduce winding wrinkles.
[0092] The operability here refers to foreign matter brought by the filter for removing foreign matter in the molten resin and foreign matter attached to the front end nozzle (T-die) of the extruder. The present invention can reduce the generation of such foreign matter.
[0093] As a method for compounding particles in the substrate film, known methods can be used in combination. For example, it can be added at any stage of the manufacture of polyester, but it is preferably added in the form of a slurry dispersed in ethylene glycol or the like at the stage after the esterification stage or the end of the transesterification reaction and before the start of the polycondensation reaction, and the polycondensation reaction is carried out. In addition, it can be carried out by a method of blending a slurry of particles dispersed in ethylene glycol or water or the like with a polyester raw material using a mixing extruder with a vent, or a method of blending dried particles with a polyester raw material using a mixing extruder, etc.
[0094] Among them, the preferred production method of the present invention is a method in which the aggregated inorganic particles are uniformly dispersed in a monomer liquid which is a part of the polyester raw material, and the filtered material is added to the remaining part of the polyester raw material before, during or after the esterification reaction. According to this method, since the monomer liquid has a low viscosity, the particles can be easily uniformly dispersed and the slurry can be filtered with high precision. At the same time, when the particles are added to the remaining part of the raw material, the dispersibility of the particles is good and new aggregates are not easily generated. From this viewpoint, it is particularly preferred to add to the remaining part of the raw material in a low temperature state before the esterification reaction.
[0095] Alternatively, the number of protrusions on the surface can be further reduced by obtaining a polyester containing particles in advance, and then kneading and extruding the pellets with pellets containing no particles (masterbatch method).
[0096] Furthermore, the base film may contain various additives within the range of the total light transmittance and the number of protrusions defined in the present invention. Examples of the additives include antistatic agents, UV absorbers, and stabilizers.
[0097] If necessary, an antistatic layer or the like may be provided on the surface opposite to the surface having the release layer, that is, on the surface of the A layer opposite to the release layer side.
[0098] (Functional layer)
[0099] The film of the present invention may preferably be provided with a functional layer on the surface of layer B on the opposite side to layer A. For example, the functional layer may be a release layer.
[0100] The functional layer is not particularly limited, and may include resins such as silicone-based, cyclic olefin-based, acyclic olefin-based, fluorine-based, alkyd-based, acrylic-based, melamine-based, and epoxy-based resins.
[0101] The silicone compound refers to a compound having a silicone structure in the molecule, and examples thereof include curable silicone, silicone grafted resin, and modified silicone resins such as alkyl-modified silicone resins.
[0102] As the reactive curable silicone resin, an addition reaction curable silicone resin, a condensation reaction curable silicone resin, an ultraviolet or electron beam curable silicone resin, or the like can be used.
[0103] Examples of the addition reaction type silicone resin include silicone resins obtained by curing polydimethylsiloxane and hydrogensiloxane with vinyl groups introduced into the terminal or side chain using a platinum catalyst. In this case, a resin that can be cured within 30 seconds at 120° C. is more preferred because it can be processed at low temperatures.
[0104] As examples, there are low-temperature addition curing types (LTC1006L, LTC1056L, LTC300B, LTC303E, LTC310, LTC314, LTC350G, LTC450A, LTC371G, LTC750A, LTC752, LTC755, LTC760A, LTC850, etc.) and thermal UV curing types (LTC851, BY24-5 10, BY24-561, BY24-562, etc.), solvent addition type (KS-774, KS-882, X62-2825, etc.) manufactured by Shin-Etsu Chemical Co., Ltd., solvent addition + UV curing type (X62-5040, X62-5065, X62-5072T, KS5508, etc.), dual curing type (X62-2835, X62-2834, X62-1980, etc.), etc.
[0105] Examples of the condensation reaction type silicone resin include a resin having a three-dimensional crosslinked structure produced by condensing polydimethylsiloxane having an OH group at the terminal and polydimethylsiloxane having an H group at the terminal using an organic tin catalyst.
[0106] As the most basic type of UV-curable silicone resin, there are resins that use the same free radical reaction as the usual silicone rubber crosslinking; resins that are photocured by introducing unsaturated groups; resins that are crosslinked by using ultraviolet rays to decompose onium salts to generate strong acids, thereby cracking epoxy groups; resins that are crosslinked by adding thiols to vinyl siloxane, etc. In addition, electron beams can also be used instead of the ultraviolet rays. The energy of electron beams is stronger than that of ultraviolet rays, and free radical-based crosslinking reactions can be carried out even without the use of initiators, as in the case of ultraviolet curing.
[0107] Examples of the resin used include UV-curing silicones manufactured by Shin-Etsu Chemical Co., Ltd. (X62-7028A / B, X62-7052, X62-7205, X62-7622, X62-7629, X62-7660, etc.), UV-curing silicones manufactured by Momentive Performance Materials, Inc. (TPR6502, TPR6501, TPR6500, UV9300, UV9315, XS56-A2982, UV9430, etc.), and UV-curing silicones manufactured by Arakawa Chemical Industries, Ltd. (Silcolease UV POLY200, POLY215, POLY201, KF-UV265AM, etc.).
[0108] As the ultraviolet curing silicone resin, acrylate-modified, glycidoxy-modified polydimethylsiloxane, etc. can also be used. These modified polydimethylsiloxanes can also be mixed with multifunctional acrylate resins, epoxy resins, etc., and used in the presence of an initiator.
[0109] The cyclic olefin resin contains a cyclic olefin as a polymerizable component. The cyclic olefin is a polymerizable cyclic olefin having an olefinic double bond in the ring, and can be divided into monocyclic olefins, bicyclic olefins, and polycyclic olefins having three or more rings.
[0110] Examples of the monocyclic olefin include cyclic C4-12 cycloolefins such as cyclobutene, cyclopentene, cycloheptene, and cyclooctene.
[0111] Examples of the bicyclic olefin include 2-norbornene; norbornenes having an alkyl group (C1-4 alkyl group) such as 5-methyl-2-norbornene, 5,5-dimethyl-2-norbornene, 5-ethyl-2-norbornene, and 5-butyl-2-norbornene; norbornenes having an alkenyl group such as 5-ethylidene-2-norbornene; norbornenes having an alkoxycarbonyl group such as 5-methoxycarbonyl-2-norbornene and 5-methyl-5-methoxycarbonyl-2-norbornene; norbornenes having a cyano group such as 5-cyano-2-norbornene; norbornenes having an aromatic group such as 5-phenyl-2-norbornene and 5-phenyl-5-methyl-2-norbornene; octahydronaphthalene; octahydronaphthalene having an alkyl group such as 6-ethyl-octahydronaphthalene, and the like.
[0112] Examples of the polycyclic olefin include dicyclopentadiene; derivatives such as 2,3-dihydrodicyclopentadiene, octahydrofluorene, dimethyl octahydronaphthalene, dimethyl cyclopentadiethylnaphthalene, and octahydrocyclopentadiethylnaphthalene; derivatives having substituents such as 6-ethyl-octahydronaphthalene; adducts of cyclopentadiene and tetrahydroindene, trimers to tetramers of cyclopentadiene, and the like.
[0113] The non-cyclic olefin resin contains non-cyclic olefin as a polymer component. Examples of the non-cyclic olefin include ethylene, propylene, 1-butene, isobutylene, 1-pentene, 2-methyl-1-butene, 3-methyl-1-butene, 1-hexene, 3-methyl-1-pentene, 4-methyl-1-pentene, 1-heptene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene and the like.
[0114] Rubber may also be used as the resin for surface treatment, and examples thereof include copolymers of butadiene, isoprene, and the like.
[0115] Regardless of whether it is a cyclic olefin or a non-cyclic olefin, the olefin-based resin may be used alone or in combination of two or more.
[0116] Cyclic olefin resins and non-cyclic olefin resins may be partially provided with hydroxyl-modified or acid-modified sites, and cross-linked with these functional groups using a cross-linking agent. The cross-linking agent may be appropriately selected according to the modified group, and for example, aromatic diisocyanates such as toluene diisocyanate, 2,4-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, xylene diisocyanate, polymethylene polyphenyl isocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, lower aliphatic diisocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, isophorone diisocyanate, alicyclic isocyanates such as hydrogenated products of the aromatic diisocyanates, melamine cross-linking agents such as methyl etherified melamine resins and butyl etherified melamine resins, epoxy cross-linking agents, etc. may be cited in addition to isocyanate cross-linking agents.
[0117] As a fluorine compound, there is no particular limitation as long as it is a compound having at least any one of a perfluoroalkyl group and a perfluoroalkyl ether group. A part of the fluorine compound can be modified by an acid, a hydroxyl group, an acrylate group, etc. A cross-linking agent can be added to cross-link the modified portion. Alternatively, a compound having at least any one of a perfluoroalkyl group and a perfluoroalkyl ether group can be added to a UV curable resin and polymerized. Alternatively, it can also be used in the form of adding a small amount of a compound having a perfluoroalkyl group without a reactive functional group to a binder resin.
[0118] As the release layer of the release film, a release agent such as a polyolefin release agent, a long-chain alkyl-containing resin release agent, a fluorine release agent, or a silicone release agent may be used as a main resin or as an additive to a binder resin.
[0119] There are no particular limitations on the binder resin, and for example, UV-curable resins obtained by curing functional groups such as acryl, vinyl, and epoxy groups by UV irradiation; ester, polyurethane, olefin, and acrylic thermoplastic resins; and epoxy, melamine, and other thermosetting resins may be used.
[0120] (resin sheet)
[0121] In particular, when the functional layer is used as a release layer, an object to be released may be laminated on the surface of the release layer. For example, a resin sheet may be mentioned as the object to be released.
[0122] In one embodiment, the release film of the present invention is not particularly limited as long as it is a resin sheet, and can be used in the manufacture of adhesives and optical films. In one embodiment, it is a release film for resin sheet molding containing an inorganic compound. Examples of the inorganic compound include metal particles, metal oxides, minerals, and the like, such as calcium carbonate, silicon dioxide particles, aluminum particles, and barium titanate particles.
[0123] Examples of the resin include polyvinyl acetal resin and poly(meth)acrylate resin.
[0124] The present invention can provide a release layer with high smoothness, and even if the resin sheet contains these inorganic compounds, it is possible to suppress defects that may be caused by the inorganic compounds, such as damage to the resin sheet and difficulty in peeling the resin sheet from the release layer.
[0125] The resin component forming the resin sheet can be appropriately selected depending on the intended use.
[0126] In one embodiment, the resin sheet containing an inorganic compound is a ceramic green sheet, an antistatic laminate or sheet, a solid battery laminate or sheet, a film capacitor laminate or sheet, etc. In other embodiments, the resin sheet can be a printed layer, a protective layer, an adhesive layer, or a layer with gaps. For example, the ceramic green sheet may contain barium titanate as an inorganic compound. In one embodiment, the thickness of the resin sheet is 0.2 μm or more and 1.0 μm or less.
[0127] Example
[0128] The present invention will be described based on the following examples, but the present invention is not limited thereto. The method for measuring the characteristic values and the method for evaluating the effects in the present invention are as follows.
[0129] (1) Particle size and distribution width in thin films
[0130] The particle-containing layer (layer A) surface was plasma treated for about 3 hours at a power of 50 W using a Plasma Reactor device manufactured by Yamato. Next, the film was metallized, and the particles not covered by the resin component were photographed from the surface of layer A at 1500 times × 10 using a scanning electron microscope (SEM), and the long side of the particles was measured as the particle size. The particles in every 20 particles were measured and the particle size distribution was calculated. Based on the results obtained, the maximum size Dmax and the minimum size Dmin of the particles in the polyester film were derived.
[0131] (2) Average void ratio
[0132] The particle size d observed in the above (1) and the long side t of the voids (void size) around the particles are measured. The obtained ratio of the particle size to the void size (t / d) is taken as the void size.
[0133] (3) Surface roughness SRp
[0134] [Method for measuring the number of large protrusions SPc(4000)]
[0135] 1. Surface morphology The surface morphology was measured in accordance with JIS-B0601 (1994) using a high-precision micro-profile measuring instrument (three-dimensional surface roughness meter) using a stylus method under the following conditions.
[0136] Measuring device: 3D micro-profile measuring instrument (Model ET4000A) manufactured by Kosaka Laboratory Co., Ltd.
[0137] Analysis instrument: Three-dimensional surface roughness analysis system (model TDA-31)
[0138] Stylus: Tip diameter 2μm, diamond
[0139] Needle pressure: 300μN
[0140] Measurement direction: Film length direction and film width direction are measured once each and averaged
[0141] X measurement length: 1250 μm
[0142] X feed speed: 0.1mm / s (measurement speed)
[0143] Y measurement length: 300 μm
[0144] Y feed pitch: 2μm (measurement interval)
[0145] Y line number: 151 (measurement number)
[0146] Z magnification: 20000 times
[0147] Low frequency cutoff: 0.25mm (fluctuation cutoff value)
[0148] High frequency cutoff: R+Wmm (roughness cutoff value)
[0149] (R+W means no cutoff.)
[0150] Filtering method: Gaussian space type
[0151] Leveling: Yes (tilt correction)
[0152] Base area: 1mm 2 .
[0153] (4) Particle shedding
[0154] The surface of the particle-containing layer of the film was observed at 600 times using a scanning electron microscope (SEM). 2 The number of particles that have fallen off is counted. The number of voids that can be seen on the film surface (≈ the number of particles that have fallen off) is observed, and the particle shedding is evaluated using the following criteria.
[0155] ○: Less than 20
[0156] △: Less than 50
[0157] ×: 50 or more
[0158] (5) Wrapping wrinkles
[0159] For each product, the number of convex wrinkles formed by air intrusion on the surface of a roll with a thickness of 18 to 50 μm, a width of 200 to 3000 mm, and a length of 4000 to 12000 m was observed and evaluated using the following reference values.
[0160] 0:0~10 or less
[0161] △: 11 to 20 or less
[0162] ×: 21 or more
[0163] (6) Pinhole evaluation
[0164] Solvent (toluene), ceramic raw material (BaTiO3, manufactured by FUJI TITANIUM INDUSTRY CO., LTD.), binder, plasticizer, etc. were mixed to form a paste, and then dispersed in a ball mill to obtain a ceramic slurry. The ceramic slurry was applied to the surface of the release layer of the release film by a doctor blade method so that the ceramic thickness becomes 1 μm when dried, and dried in an oven at an ambient temperature of 100°C for 5 minutes to obtain a ceramic sheet. A 10 cm thick sheet was placed 10 cm from the opposite side of the sheet. 2 Light was irradiated over a certain area, and the occurrence of pinholes was observed and evaluated using the following criteria.
[0165] In addition, the mold release layer was laminated on the layer B. The main components contained in the mold release layer are as described in Example 1 mentioned later.
[0166] ×: There are many pinholes.
[0167] △: There are almost no pinholes.
[0168] ○: No pinhole.
[0169] (Example 1)
[0170] (Preparation of polyethylene terephthalate pellets (a) containing calcium carbonate particles)
[0171] Calcium carbonate particles (manufactured by Maruo Calcium Co., Ltd.) having an average particle size of 0.6 μm as measured by a light transmission type particle size distribution measuring apparatus (manufactured by Shimadzu Corporation, SA-CP3) were added to ethylene glycol, and further filtered using a viscose rayon filter having a 95% retention diameter of 30 μm to obtain an ethylene glycol slurry of the calcium carbonate particles.
[0172] The following method is used to obtain polyethylene terephthalate (a) containing calcium carbonate particles. The temperature of the esterification reaction tank is raised to 200°C, and a slurry formed by 86.4 parts by weight of terephthalic acid and 64.4 parts by weight of ethylene glycol is added. While stirring, 0.03 parts by weight of antimony trioxide, 0.088 parts by weight of magnesium acetate tetrahydrate, and 0.16 parts by weight of triethylamine as catalysts are added. Next, the pressure is increased and the temperature is raised to 3.5 kgf / cm 2 , 240°C, a pressurized esterification reaction is carried out. Then, the pressure in the esterification reaction tank is returned to normal pressure, and 0.040 parts by weight of trimethyl phosphate is added. Furthermore, the temperature is raised to 260°C, and 15 minutes after the addition of trimethyl phosphate, an ethylene glycol slurry of the above-mentioned calcium carbonate particles is added to the generated polyester so as to become 20,000 ppm. After 15 minutes, the obtained esterification reaction product is transferred to a polycondensation reaction tank, and a polycondensation reaction is carried out under reduced pressure at 280°C. After the polycondensation reaction is completed, a 95% cutoff diameter 28μm nitrile filter (manufactured by Nippon Seisen Co., Ltd.) is used for filtration treatment to obtain a polyethylene terephthalate masterbatch (a) containing calcium carbonate particles having a characteristic viscosity of 0.62dl / g.
[0173] (Preparation of polyethylene terephthalate pellets (b))
[0174] As the esterification reaction apparatus, a continuous esterification reaction apparatus consisting of a stirring device, a condenser, and a three-stage complete mixing tank with a raw material input port and a product output port was used. TPA was set to 2 tons / hr, EG was set to 2 moles relative to 1 mole of TPA, and antimony trioxide was set to an amount of 160 ppm of Sb atoms relative to the generated PET. These slurries were continuously supplied to the first esterification reaction tank of the esterification reaction apparatus, and the reaction was carried out at 255°C under normal pressure with an average residence time of 4 hours.
[0175] Next, the reaction product in the first esterification reaction tank was continuously taken out of the system and supplied to the second esterification reaction tank, and EG distilled from the first esterification reaction tank was supplied to the second esterification reaction tank in an amount of 8 wt % relative to the produced polymer (produced PET), and an EG solution containing 65 ppm of magnesium acetate and 20 ppm of TMPA relative to the produced PET were further added to react at 260° C. under normal pressure with an average residence time of 1.5 hours.
[0176] Next, the reaction product in the second esterification reaction tank was continuously taken out of the system and supplied to the third esterification reaction tank, and an EG solution containing TMPA in an amount of 20 ppm of P atoms relative to the generated PET was further added, and the reaction was carried out at 260° C. under normal pressure with an average residence time of 0.5 hours.
[0177] The esterification reaction product generated in the above-mentioned third esterification reaction tank is continuously supplied to a three-stage continuous polycondensation reaction device for polycondensation, and further filtered with a stainless steel sintered body filter material (nominal filtration accuracy 5μm particles 90% retention) to obtain polyester pellets (b) with an intrinsic viscosity of 0.620dl / g.
[0178] (Manufacture of polyester film)
[0179] The masterbatch (a) was diluted with pellets (b) of polyethylene terephthalate containing no particles at a predetermined ratio, dried under reduced pressure (3 Torr) at 180°C for 8 hours, and then supplied to extruder 1. The pellets (b) of polyethylene terephthalate containing no particles were supplied to extruder 2, and the intermediate layer was supplied to extruder 3 and dissolved at 285°C. The three polymers were filtered using a filter material of a sintered stainless steel body (nominal filtration accuracy, 95% retention of particles of 10 μm), stacked using a three-layer confluence block having a rectangular stacking portion, extruded from a nozzle in a sheet form, and then wound on a casting drum with a surface temperature of 30°C using an electrostatic casting method, and cooled and solidified to form an unstretched film.
[0180] The unstretched film was stretched to 3.3 times in the longitudinal direction at 85° C., then the uniaxial film was stretched 4.0 times in the width direction by a tenter, and heat-treated at 230° C. for 5 seconds to obtain a laminated film with a total thickness of 31 μm, wherein the ratio of the layer (A) containing calcium carbonate particles was 20%, the ratio of the layer (B layer) containing substantially no particles was 40%, and the ratio of the intermediate layer was 40%. The particle content of the layer (A) containing calcium carbonate particles at this time was 5000 ppm.
[0181] Next, a UV cation-curable silicone resin (manufactured by Toshiba Silicone Co., Ltd., UV9315) was dispersed in a solvent (n-hexane) at a resin solid content concentration of 2 wt%, and 1 part by weight of bis(alkylphenyl)iodonium hexafluoroantimony salt was added as a curing catalyst to 100 parts by weight of the silicone resin to prepare a coating liquid containing the silicone resin. The coating liquid containing the silicone resin was applied to the surface of the B layer of the laminated film using a wire rod, dried at 100°C for 30 seconds, and then irradiated with ultraviolet light (300 mj / cm 2 ) to obtain a ceramic release polyester film (the coating amount of the silicone release layer after drying is 0.10 g / m 2 ).
[0182] Tables 1 and 2 show the evaluation results.
[0183] The particles in the thin film obtained in Example 1 showed a relationship of 0.5≤(Dmax-Dmin)≤5.5.
[0184] (Example 2)
[0185] A biaxially stretched polyester film was prepared in the same manner as in Example 1 except that the average particle size of the particles contained in PET was changed to 0.9 μm and divided by The particles in the film obtained in Example 2 showed a relationship of 0.5≤(Dmax-Dmin)≤5.5.
[0186] (Example 3)
[0187] A biaxially stretched polyester film was prepared in the same manner as in Example 1 except that the film thickness was changed to 25 μm and divided by .
[0188] (Example 4)
[0189] A biaxially stretched polyester film was prepared by the same method as in Example 1, except that the film thickness was changed to 19 μm and divided by .
[0190] (Example 5)
[0191] A biaxially stretched polyester film was prepared in the same manner as in Example 1 except that the average particle size of the particles contained in PET was changed to 1.2 μm and divided by . The particle size distribution obtained in Example 5 was 0.3 μm or more and 6.0 μm or less.
[0192] (Example 6)
[0193] A biaxially stretched polyester film was prepared in the same manner as in Examples 1 and 2 except that the amount of particles added in Example 2 was changed to 3000 ppm and divided by.
[0194] (Example 7)
[0195] A biaxially stretched polyester film was prepared in the same manner as in Examples 1 and 2 except that the amount of particles added in Example 2 was changed to 8000 ppm and divided by.
[0196] (Example 8)
[0197] A biaxially stretched polyester film was produced in the same manner as in Example 2 except that the intermediate layer contained 400 ppm of calcium carbonate having an average particle size of 0.9 μm.
[0198] (Comparative Example 1)
[0199] A biaxially stretched polyester film was prepared in the same manner as in Example 1 except that the calcium carbonate particles had an average particle size of 0.2 μm and the result was divided by . The particles in the obtained film did not show a relationship of 0.5 ≤ (Dmax - Dmin) ≤ 5.5.
[0200] (Comparative Example 2)
[0201] A biaxially stretched polyester film was prepared in the same manner as in Example 1 except that the average particle size of the calcium carbonate particles was changed to 1.5 μm and divided by . The particles in the obtained film did not show a relationship of 0.5≤(Dmax-Dmin)≤5.5.
[0202] (Comparative Example 3)
[0203] A biaxially stretched polyester film was prepared in the same manner as in Example 1 except that the average particle size of the calcium carbonate particles was changed to 2.0 μm and divided by . The particles in the obtained film did not show a relationship of 0.5≤(Dmax-Dmin)≤5.5.
[0204] (Reference Example 4)
[0205] (Preparation of Polyethylene Terephthalate Pellets Containing Silica Particles)
[0206] In the same manufacturing method as in Example 8, only 1.0 μm silica (manufactured by Nippon Shokubai Co., Ltd.) was used to obtain silica-containing pellets with a silica concentration of 5%. Furthermore, a biaxially stretched polyester film was prepared by the same film-making method as in Example 1. It should be noted that in Reference Example 4, the distribution of the particle size contained in the film was extremely small, and the distribution of the particle size was actually concentrated near the average particle size. Reference Example 7 showed a tendency for the particles to slide off.
[0207] (Reference Example 5)
[0208] (Preparation of Polyethylene Terephthalate Pellets Containing Silica Particles)
[0209] In the same manufacturing method as in Example 8, only 1.2 μm silica (manufactured by Nippon Shokubai Co., Ltd.) was used to obtain silica-containing pellets with a silica concentration of 5%. Furthermore, a biaxially stretched polyester film was prepared by the same film-making method as in Example 1. It should be noted that in Reference Example 5, the distribution of the particle size contained in the film was extremely small, and the distribution of the particle size was actually concentrated near the average particle size. Reference Example 5 showed a tendency for the particles to slide off.
[0210] Table 1
[0211]
[0212] Table 2
[0213]
[0214] Comparative Examples 1 to 3 contained particles with a particle size distribution of less than 0.3 μm and / or particles larger than 6.0 μm, and could not achieve suppression of winding wrinkles or suppression of pinholes.
[0215] On the other hand, in the present invention, for example, coarse protrusions can be suppressed, winding wrinkles can be suppressed, the formation of pinholes caused by the transfer of coarse protrusions on the reverse demolding surface to the demolding surface side can be suppressed, the falling of particles from the surface layer of the film can be suppressed, and the formation defects caused by the deterioration of the planarity of the demolding surface side can be suppressed.
[0216] Industrial Applicability
[0217] The present invention can provide a biaxially oriented laminated polyester film capable of suppressing the generation of pinholes more effectively than the conventional art in the production process of a resin sheet such as a ceramic green sheet.
Claims
1. A biaxially oriented laminated polyester film used as a release film for forming a resin sheet, the biaxially oriented laminated polyester film comprising an A layer and a B layer, The A layer contains particles, The maximum peak height (SRp) of the surface roughness of the A layer is 1.0 μm or less, The relationship between the maximum size Dmax and the minimum size Dmin of the particles in the polyester film satisfies the following formula 1: 0.5 μm ≤ (Dmax - Dmin) ≤ 5.5 μm (Formula 1).
2. The biaxially oriented laminated polyester film according to claim 1, wherein The B layer is a layer that substantially does not contain particles having a particle size of 1.0 μm or more. The maximum peak height SRp of the surface of the B layer is 1.0 μm or less.
3. The biaxially oriented laminated polyester film according to claim 1, wherein The ratio of the void size t in the film to the average particle size d satisfies the following equation 2: 0.5≤t / d≤3.0 (Formula 2).
4. The biaxially oriented laminated polyester film according to claim 1, wherein The film thickness is 12 μm or more and 50 μm or less.
5. A release film comprising the biaxially oriented laminated polyester film according to any one of claims 1 to 4 and a functional layer, The functional layer is disposed on the layer B side of the biaxially oriented laminated polyester film.
Citation Information
Patent Citations
Manufacturing method of laminated ceramic electronic parts
JP2003133170A